Profil of Concept Understanding Of Cross-Interest Class Students on Fungi Materials at SMA N 1 Sungai Raya During the Covid-19 Pandemic - Ade Wulandari; Arif Didik Kurniawan; Ari Sunandar (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2021)
Background: Education is very important in advancing a nation. Understanding is obtained when learning activities take place. However, with the Covid-19 pandemic condition, the government issued an online system learning policy, this will affect students' understanding of concepts, especially in biology subjects. Based on the results of a pre-research questionnaire given to biology teachers at SMA N 1 Sungai Raya, the completeness of cross-interest class students in Fungi material was less than 70% in the year before the covid-19 pandemic. The purpose of this study was to describe the understanding of the concept of cross-interest class students on Fungi material at SMA N 1 Sungai Raya during the covid-19 pandemic. Methods: This type of research is descriptive qualitative. The research subjects were students of class X cross-interest at SMA N 1 Sungai Raya. The method used is to provide a two tier test instrument through the google form application. Results: The results showed that 41% of students understood the concept, 24% of students who had misconceptions, 15% of students who guessed, and 20% of students who did not understand the concept. Keywords : Concept Understanding; Cross-Interest Classes; Fungic Matter; Covid-19 Pandemic